PEDAGOGICAL MODEL OF DEVELOPING CONVERGENT COMPETENCE IN FUTURE TEACHERS (Universal International Scientific Journal, 2026)
This thesis develops the theoretical and methodological foundations for theformation of convergent competence in future teachers and proposes a pedagogical model aimed at itsimplementation. The study extensively examines the need to elevate teacher professional training to anew level within the modern educational system, where the importance of interdisciplinary integration,problem-based thinking, and reflective practice is steadily increasing. In the thesis, convergentcompetence is interpreted as the ability to integrate pedagogical, psychological, and methodologicalknowledge, to make innovative and well-grounded decisions in complex pedagogical situations, and toconduct systematic analysis of professional activity.
Keywords: convergent competence; future teacher; pedagogical model